Construction, validity, and reliability of the Scale of Readiness for Change (SRCAA) in adults with alcoholism - Mestas-Mamani, Angie Lizet (2025)
Introduction: To establish better approaches to alcoholism, this scale was developed with a focus on cognitive-behavioral aspects. Objective: Considering alcoholism as an issue that requires self-efficacy attention, the scale is designed to guide the psychotherapist in the behavioral change process of the alcoholic patient. Method: This psychometric research, with a non-experimental mixed-method descriptive design, is delineated by a non-probabilistic sampling method that employs structural equation modeling for an infinite sample. Using statistical software, the Aiken's V was obtained from seven expert judges, and 20 items were considered in the exploratory factor analysis for factor loadings (two factors) and factorial weights (λ = 0.62 - λ = 0.94), with Kaiser-Meyer-Olkin and Bartlett's test of sphericity results (KMO = 0.96, p < 0.01). Results: A two-factor model was found with adequate goodness-of-fit values (CFI = 0.987; TLI = 0.985; SRMR = 0.073; RMSEA = 0.077), with the removal of item C11 due to its low factorial loading (λ = 0.24). The scale, which contains 19 items and 2 factors, shows a good reliability coefficient (Cronbach's Alpha and McDonald's Omega ranging from 0.801 to 0.963). In terms of convergent validity, a strong inverse correlation (Rho = -0.670; p = 0.000) was found between the SRCAA and GAD-7. Conclusion: Based on these statistical findings, the scale demonstrates that it meets the objective of identifying the degree of awareness regarding alcohol consumption and the behavioral changes a person makes to overcome the detrimental habit.